Pengaruh Pelayanan Terhadap Kepuasan Pelanggan Pada Angkringan Abah Agus Karawang: Pengaruh Pelayanan Terhadap Kepuasan Pelanggan Pada Angkringan Abah Agus Karawang - Moch Agus Ariffianto Agus; Rian Permana Suryadipraja; Rohma Septiawati; Arman Paramansyah (Muttaqien Publishing, Lembaga Penelitian dan Pengabdian kepada Mayarakat (P3M) STAI DR. KH.EZ. Muttaqien Purwakarta, 2021)
This study will discuss about the Angkringan service process on customer satisfaction. In line with this problem, this research was carried out using qualitative research with descriptive analysis methods, namely research by focusing on certain aspects and showing the relationship between various variables, then conducting descriptions to provide a clear picture. Based on the results of the analysis on Angkringan Abah Agus Karawang, it can be concluded that the value of the correlation coefficient between the two variables X and variable Y where the resulting value r = 0.51 has a strong enough relationship, and is based on the regression coefficient Y = 31.16 + 7.5 X, meaning that if the X value increases, the Y value will be even greater. This has been proven through the F test, where the F test results show that the F-count> F-table which in this study has been proven and acceptable. And customer satisfaction, has a positive and significant effect, it means that the two variables in this study are not the more dominant variables so that they are declared unproven and unacceptable. Based on these findings, Angkringan Abah Agus Karawang suggested the need to improve the quality of services provided as a stimulus to increase customer satisfaction of angkringan and to get the expected customer satisfaction. There is also a need for a periodic assessment process for the services provided as a measure of appropriate satisfaction for customers.